Insulin Resistance is a Risk Factor for Early Miscarriage and Macrosomia in Patients With Polycystic Ovary Syndrome From the First Embryo Transfer Cycle: A Retrospective Cohort Study - Chen, Yuanhui; Guo, Jiayu; Zhang, Qingwen; Zhang, Cuilian (Frontiers in Endocrinology, 2022)
Objective The objective of the study was to explore the effect of insulin resistance on pregnancy outcomes in patients with polycystic ovary syndrome (PCOS) from the first embryo transfer cycle. Design This was a single-center, retrospective, observational cohort study. Patients Included in the study were women with PCOS for the first embryo transfer. Main Outcome Measures Early miscarriage rate and macrosomia rate were the main outcome measures. Results With increased HOMA-IR, the early miscarriage rate (7.14, 13.21, and 16.22%, respectively; P = 0.039), macrosomia rate (5.78, 11.79, and 17.58%, respectively; P = 0.026) and the incidence of gestational diabetes (GDM) (10.00, 14.50, and 25.67% respectively; P = 0.002) significantly increased, while the live birth rate markedly decreased (63.03, 55.27, and 47.88%, respectively; P = 0.004). No significant difference was found in clinical pregnancy rate, late miscarriage rate, low birthweight rate and baby gender ratio (all P >0.05). After adjusting for confounding factors, HOMA-IR was an independent risk factor of early miscarriage rate and macrosomia rate. Conclusion Insulin resistance is an independent risk factor for early miscarriage and macrosomia in PCOS patients during the first embryo transfer cycle. It is essential to give more attention before and after pregnancy for PCOS women with high HOMA-IR.